The Role of Teaching Practicum and Classroom Management Training in Preparing Early-Career Educators in Bangladesh: A Reflective Qualitative Study - Alam, Sanzida; Hasan, Md. Mahadhi (Universitas Islam Negeri Raden Intan Lampung, 2025)
Within the context of the emerging 21st-century educational paradigm, traditional pedagogical approaches and classroom management strategies increasingly become inadequate to respond effectively to the emerging complex issues in the classrooms generated by diversity in student populations. Precisely, this study aims at exploring the complex challenges that beginning teachers face in Bangladesh and will particularly investigate their instructional strategies and classroom management. Based on a qualitative methodological framework, this study relies on data collected through reflective journaling, note-taking, peer discussions, and instructional observations. The findings underline the crucial importance of micro-teaching, along with reflective lesson planning and material design, combined with a basic acquaintance with Second Language Acquisition (SLA) theories. The combination of these elements, with a structured approach to peer feedback and self-reflection, has shown the potential of increasing the teaching competencies needed for 21st-century English language classrooms in Bangladesh. Furthermore, this study has shown the requirement for the development of clear teaching philosophies, appropriate choices regarding pedagogical resources, the use of multi-modal teaching methods, and being student-centered—all of which have been associated with improved learning outcomes. This study therefore also found that micro-teaching sessions could be an essential vehicle for improving the pedagogical methods and professional competencies of teachers. It therefore encourages the systematic introduction of teaching practicums coupled with classroom management training as core structures for teacher preparation and lifelong professional development in Bangladesh and in broader educational settings.